Tailored online cognitive behavioural therapy with or without therapist support calls to target psychological distress in adults receiving haemodialysis: A feasibility randomised controlled trial. - Hudson, J; Moss-Morris, R; Norton, S; Picariello, F; Game, D; Carroll, A; Spencer, J; McCrone, P; Hotopf, M; Yardley, L; Chilcot, J (Elsevier, 2017)
Background Psychological distress is prevalent in haemodialysis (HD) patients yet access to psychotherapy remains limited. This study assessed the feasibility and acceptability of online cognitive-behavioural therapy (CBT) tailored for HD patients, with or without therapist support, for managing psychological distress. Methods This feasibility randomised controlled trial recruited patients from a UK HD centre. Following psychological distress screens, patients with mild-moderate psychological distress (Patient Health Questionnaire PHQ-9; score: 5–19 and/or Generalised Anxiety Disorder; GAD-7 score: 5–14) who met remaining inclusion criteria were approached for consent. Consenters were individually randomised (1:1) to online-CBT or online-CBT plus three therapist support calls. Outcomes included recruitment, retention, and adherence rates. Exploratory change analyses were performed for: psychological distress, quality of life (QoL), illness perceptions, and costs. The statistician was blinded to allocation. Results 182 (44%) out of 410 patients approached completed psychological distress screens. 26% found screening unacceptable; a further 30% found it unfeasible. Psychological distress was detected in 101 (55%) patients, 60 of these met remaining inclusion criteria. The primary reason for ineligibility was poor computer literacy (N = 17, 53%). Twenty-five patients were randomised to the supported (N = 18) or unsupported arm (N = 7); 92% were retained at follow-up. No differences in psychological distress or cost-effectiveness were observed. No trial adverse events occurred. Conclusions Online CBT appears feasible but only for computer literate patients who identify with the label psychological distress. A definitive trial using the current methods for psychological distress screening and online care delivery is unfeasible.